DNA loop organization in glioblastoma T98G cells at their different functional states - Afanasieva, K.S.; Semenova, A.Y.; Lukash, L.L.; Sivolob, A.V. (Вiopolymers and Cell, 2018)
The loop domain organization of chromatin, which plays an important role in transcription regulation, may depend on the cell functional state. Aim. To investigate DNA loop reorganization upon functional transitions in the glioblastoma T98G cells. Methods. Single cell gel electrophoresis (a comet assay) was used to analyze the kinetics of the DNA loop migration from the nucleoids obtained from the lysed cells. Results. The cells arrested in the G1 phase of the cell cycle were characterized by a relatively low amount of DNA in the comet tails due to a low content of DNA in the loops which may be resolved by the comet assay (up to ~300 kb). After cell reactivation, the contour length of the loops essentially increased in parallel with a decrease in the linear loop density along the genome. Conclusions. An increase in the loop size and a respective decrease in the loop density may be a general feature of activated cells as we earlier observed similar effects upon activation of human lymphocytes.